Tropos en la poesía aborigen Ecuatoriana. - Altamirano Escobar, Erika Jazmín (2024)
The study called “Tropes in Ecuadorian Aboriginal Poetry” had as its general objective to analyze the literary value of the tropes used in the Aboriginal poetry of present-day Ecuador. The present work was carried out using a qualitative approach, so information was collected, and its design is non-experimental because it does not have random determination, manipulation of variables or comparison groups. The literary corpus of this research is the poem “Elegy to the death of Atahualpa” written by Jacinto Collahuazo and rescued by Juan León Mera in his work Historical-critical overview of Ecuadorian poetry in 1868 and valued as an example of Quechua poetry originating in Ecuadorian territory. On the other hand, the Literary Tropes analysis matrix was used to facilitate the identification, classification, and analysis of these tropes. The analysis of the poem supported by the matrix allowed to recognize the tropes, the cultural context, the meaning in the work, the elements and the sociocultural impact. The result of this analysis shows how the poem articulates both personal and collective pain, where the figure of Atahualpa is central to understanding the impact of the conquest on Andean cultures. Likewise, the sociocultural context shows the implicit criticism of colonization and a vindication of Indigenous culture